Arabidopsis Lunapark proteins are involved in ER cisternae formation. Issue 3 (25th May 2018) - Kriechbaumer, Verena; Breeze, Emily; Pain, Charlotte; Tolmie, Frances; Frigerio, Lorenzo; Hawes, Chris
Summary: The plant endoplasmic reticulum (ER) is crucial to the maintenance of cellular homeostasis. The ER consists of a dynamic and continuously remodelling network of tubules and cisternae. Several conserved membrane proteins have been implicated in formation and maintenance of the ER network in plants, such as RHD3 and the reticulon proteins. Despite the recent work in mammalian and yeast cells, the detailed molecular mechanisms of ER network organization in plants remain largely unknown. Recently, novel ER network‐shaping proteins called Lunapark (LNP) have been identified in yeast and mammalian cells. Here we identify two Arabidopsis LNP homologues and investigate their subcellular localization via confocal microscopy and potential function in shaping the ER network using protein–protein interaction assays and mutant analysis. We show that AtLNP1 overexpression in tobacco leaf epidermal cells mainly labels cisternae in the ER network, whereas AtLNP2 labels the whole ER. Overexpression of LNP proteins results in an increased abundance of ER cisternae and lnp1 and lnp1lnp2 amiRNA lines display a reduction in cisternae and larger polygonal areas. Thus, we hypothesize that AtLNP1 and AtLNP2 are involved in determining the network morphology of the plant ER, possibly by regulating the formation of ER cisternae.